Boosting lithium-ion transport capability of LAGP/PPO composite solid electrolyte via component regulation from 'Ceramics-in-Polymer' to 'Polymer-in-Ceramics'. Issue 18 (15th September 2022) - Huang, Zhen-hao; Li, Jie; Li, Lin-xin; Xu, Hui-min; Han, Chong; Liu, Ming-quan; Xiang, Jun; Shen, Xiang-qian; Jing, Mao-xiang
Abstract: The design and regulation of the ion transport channels in the polymer electrolyte is an important means to improve the lithium ion transport behavior of the electrolyte. In this work, we for the first time combined the high ionic conductive inorganic ceramic electrolyte Li1.5 Al0.5 Ge1.5 (PO4 )3 (LAGP) with flexible polypropylene oxide (PPO) polymer electrolyte to synthesize a high-filling LAGP/PPO composite solid electrolyte film and regulated the ion transport channels from 'Ceramics-in-Polymer' mode to 'Polymer-in-Ceramics' mode by optimizing the ratio of LAGP vs. PPO. The results reveal that when the LAGP content <40%, the electrolyte belongs to 'LAGP-in-PPO', and then changes to 'PPO-in-LAGP' when the LAGP content exceeds 40%. Compared with 'LAGP-in-PPO', the 'PPO-in-LAGP' shows better comprehensive properties, especially for the 75% LAGP-filled PPO electrolyte, the room-temperature ionic conductivity is as high as 3.46 × 10 −4  Scm −1, the ion migration number and voltage stable window reach 0.83 and 4.78 V respectively. This high-filled composite electrolyte possesses high tensile stress of 40 MPa with a strain of 46% and withstands working environment up to 200 °C. The NCM622/Li solid-state battery composed of this electrolyte also presents good rate and cycle performances with a capacity retention of 80% after 230 cycles at 0.3C because of its high ion transport capability and good inhibition of lithium dendrites. This composite structural design is expected to develop high-performance solid-state electrolytes suitable for high-voltage solid-state lithium batteries.